Health-Seeking Behavior of Dengue Hemorrhagic Fever Patients in Several Hospitals in Bandung West Java Indonesia - Ressa Novita Afandi; Bachti Alisjahbana; Ardini S. Raksanagara (Faculty of Medicine Universitas Padjadjaran, 2018)
Background: Dengue hemorrhagic fever is one of the major global public health problems. Secondary prevention of dengue fever must be conducted to prevent high mortality rate by giving appropriate diagnosis and early management. This study was conducted to identify health-seeking behavior in dengue hemorrhagic patients and its related factors.Methods: This study involved 98 dengue hemorrhagic patients from four hospitals in Bandung region during July until November 2014. The hospitals were 2 public hospitals and 2 private hospitals. A questionnaire and in depth interview were used to collect the data.Results: Among 98 patients, 54 patients (55%) sought a right medical treatment timely, whereas 44 patients (45%) delayed. The first seeking behaviour to treat the disease was using over-the-counter drugs, followed by visiting a private clinic doctor. The second choice to seek health care was going to a private clinic doctor and hospital.Conclusions: Health-seeking behavior in dengue hemorrhagic patients in Bandung is inappropriate which can cause delay in treatment.